2016
DOI: 10.1007/s10549-016-3765-4
|View full text |Cite
|
Sign up to set email alerts
|

Informing hot flash treatment decisions for breast cancer survivors: a systematic review of randomized trials comparing active interventions

Abstract: Patient-centered decision making about hot flash treatments often incorporates a balance of efficacy and side effects in addition to patient preference. This systematic review examines randomized controlled trials (RCTs) comparing at least two non-hormonal hot flash treatments in breast cancer survivors. In July 2015, PubMed, SCOPUS, CINAHL, Cochrane, and Web of Science databases were searched for RCTs comparing active, non-hormonal hot flash treatments in female breast cancer survivors. Thirteen trials were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 60 publications
0
46
1
3
Order By: Relevance
“…21,23,24,5459 Phytoestrogens, botanicals, and dietary supplements can also be used (category 2B for all); however, data are mixed or limited on the effectiveness and safety of these particular treatments in the general menopausal population and in cancer survivors. 22,6067 Vitamin E has been thought to have marginal improvement in vasomotor symptoms in both general menopause and patients with breast cancer, but data are limited and have shown mixed results.…”
Section: Menopausementioning
confidence: 99%
“…21,23,24,5459 Phytoestrogens, botanicals, and dietary supplements can also be used (category 2B for all); however, data are mixed or limited on the effectiveness and safety of these particular treatments in the general menopausal population and in cancer survivors. 22,6067 Vitamin E has been thought to have marginal improvement in vasomotor symptoms in both general menopause and patients with breast cancer, but data are limited and have shown mixed results.…”
Section: Menopausementioning
confidence: 99%
“…Those taking tamoxifen as endocrine therapy or high-risk women taking tamoxifen to reduce their breast cancer risk 62 should avoid the SSRIs fluoxetine and paroxetine since these impair conversion of tamoxifen to its active metabolite, potentially diminishing its efficacy. 34 A randomised trial comparing the SNRI venlafaxine (extended release, 75 mg/day) with 0.5 mg/day oral 17β oestradiol found that both treatments were associated with a statistically significant reduction in the frequency of vasomotor symptoms of around 50% after eight weeks of use. 63 Oestradiol improved menopause-related quality of life (as measured by the MENQOL 64 ) more than venlafaxine.…”
Section: Serotonin Selective Reuptake Inhibitors and Serotonin And Nomentioning
confidence: 99%
“…Desvenlafaxine 100 mg/day is the active metabolite of venlafaxine and reduces vasomotor symptoms for up to 12 months. 34 Desvenlafaxine is not available in the UK.…”
Section: Serotonin Selective Reuptake Inhibitors and Serotonin And Nomentioning
confidence: 99%
See 1 more Smart Citation
“…5 Second, antidepressants are often co-prescribed with tamoxifen for extended periods, 6 in part because depression often coexists with breast cancer and in part to offset vasomotor symptoms induced by tamoxifen. 7 Third, and in contrast with most drug interactions, the consequences are delayed by years and manifest simply as treatment failure, undermining causal attribution at the patient level.…”
mentioning
confidence: 99%